Clinical relevance of an unfused pancreatic duct system. Issue 12 (December 1979) - Mitchell, C J; Lintott, D J; Ruddell, W S; Losowsky, M S; Axon, A T
Abstract : In man, the main pancreatic duct is normally derived from ventral and dorsal embryological buds of the pancreas. In a minority of people, failure of fusion of the two buds results in separate drainage of the dorsal and ventral pancreas, so that the accessory duct provides the main drainage for the gland. Patients with this anomaly demonstrated at endoscopic retrograde pancreatography (ERP) have been investigated to assess whether non-fusion of the main pancreatic duct predisposes to the development of pancreatitis. A failure of fusion of the pancreatic ducts was seen in 21 out of 449 (4.7%) successful pancreatograms; four of these 21 patients had definite clinical evidence of pancreatitis and two patients had possible pancreatic disease, but in the remainder the anomaly was not considered to be clinically relevant. An abnormal pancreatogram suggesting pancreatitis was present in 116 out of the 428 patients (27.1%) with a normally fused duct system. The anomaly was found as frequently in the whole series as it was seen in patients with pancreatitis. These findings suggest that embryological failure of pancreatic duct fusion does not predispose to the development of pancreatitis. However, the presence of this anomaly may lead to misinterpretation of ultrasonographic and CT scan findings.